Вплив параметрів процесу на алкоголіз соняшникової олії етиловим спиртом - Палюх, Зоряна Юріївна; Мельник, Юрій Романович; Мельник, Степан Романович (НТУ "ХПІ", 2016)
Визначено вплив технологічних параметрів процесу на алкоголіз соняшникової олії етиловим спиртом у присутності каталізаторів – катіоніту КУ-2-8 у Н-формі та з іммобілізованими іонами Со²⁺. Встановлено, що оптимальною температурою процесу є 353К. Показано, що частота перемішування 80 об/хв і більше не впливає на швидкість реакції і максимальну конверсію олії. Встановлено, що для досягнення максимальної конверсії олії мольне співвідношення етанол : триолеат гліцерину повинно становити не менше, ніж 4,5 : 1. Показано, що наявність 5-10 мас. % води у спирті дозволяє підвищити кінцеву конверсію соняшникової олії на 5-10%. Виявлено екстремальну залежність максимальної конверсії триолеату гліцерину від вмісту каталізатора у реакційній суміші.

The aim of research was to study the influence of technological parameters of transesterefication of sunflower oil with ethyl alcohol on the conversion of glycerol trioleate. The influence of reaction temperature, catalyst concentration, intensity of mixing of the reaction mixture, the molar ratio ethanol: glycerol trioleate, the water content in the reaction mixture on the transesterification process of sunflower oil with ethyl alcohol and with catalysts – cation exchange resin KU-2-8 in H-form and the immobilized form with Co²⁺ -ions has been determined. It has been established that the optimal temperature of process is 353K. It has been shown that mixing with frequency over 80 min–1 has no affects on the reaction rate and the maximum conversion of sunflower oil. It was found that to maximize the conversion of glycerol trioleate the molar ratio ethanol : glycerol trioleate should be not less than 4.5 : 1. It has been shown that the presence of 5-10 wt. % water in alcohol can increase the final conversion of sunflower oil on 5-10%. The extreme dependence of maximum conversion of glycerol trioleate from the content of catalyst in the reaction mixture has been discovered. The established optimal conditions of transesterifications process of sunflower oil with ethyl alcohol allowed to achieve almost complete conversion of glycerol trioleate.
The effect of parameters on the transesterification process of sunflower oil with ethanol
Keywords: алкоголіз; етанол; триолеат гліцерину; катіоніт; glycerol trioleate; cation exchange resin